What drives the short-term fluctuations of banks' exposure to interest rate risk? - Christoph Memmel (Review of Financial Economics, 2020)
We investigate whether banks actively manage their exposure to interest rate risk in the short run. Using bank-level data of German banks for the period 2011Q4–2017Q2, we find evidence that banks actively manage their interest rate risk exposure in their banking books. Specifically, they adjust their exposure to the earning opportunities presented by this risk, take account of their regulatory situation, and manage this exposure using interest swaps. We also find that the fixed-interest period of housing loans has an impact on the banks' overall exposure to interest rate risk. This last finding, in combination with the empirical evidence that customer preferences predominantly determine the fixed-interest period of these loans, is not in line with active interest rate risk management.
Keywords: 330; fixed-interest period of housing loans; interest rate risk in the banking book; interest swaps; regulation of interest rate risk